Positive experiences of family caregivers of patients with chronic heart failure: protocol for a qualitative systematic review and meta-synthesis - Panpan Yang; Qingyi Guan; Mengzhen Ma; Yanyan Fan (BMJ Open)
Introduction Previous studies have highlighted the experiences of caregivers for patients with chronic heart failure (CHF), specifically focusing on their negative experiences. There are few systematic reviews on the topic to synthesise the positive experiences of family caregivers for patients with CHF. This study will examine how experiences such as developing new skills, strengthening their relationships (between caregivers and recipients) and receiving appreciation from the care recipient assist to improve caregivers’ perception of their circumstances.Methods and analysis This review will be conducted in accordance with the Joanna Briggs Institute (JBI) methodology for qualitative systematic reviews. Qualitative and mixed methods studies related to the positive experiences of family caregivers for patients with CHF, reported in English or Chinese and published from inception in the following databases will be included: PubMed, MEDLINE, Embase, Cochrane Library, Web of Science, PsycINFO, CINAHL, Wan Fang Data, China National Knowledge Infrastructure, Chongqing VIP, Chinese Biomedical Literature Database, Open Grey and Deep Blue Library databases. The standard JBI Critical Appraisal Checklist for Qualitative Research will be used by two independent reviewers to appraise the quality of the included studies, and the standardised JBI Qualitative Data Extraction Tool for Qualitative Research will be applied to extract data. The final synthesised findings will be graded according to the ConQual approach for establishing confidence in the output of qualitative research synthesis.Ethics and dissemination Ethical approval is not required as no primary data are being collected. The results will be made available through a peer-reviewed publication.PROSPERO registration number CRD42021282159.